A comparative study of effects of dietary mercuric chloride and methylmercury chloride on growth performance, tissue accumulation, stress and immune responses, and plasma measurements in Korean rockfish, Sebastes schlegeli. (December 2020) - Jang, Ji-Won; Lee, Seunghyung; Lee, Bong-Joo; Hur, Sang-Woo; Son, Maeng-Hyun; Kim, Kang-Woong; Kim, Kyoung-Duck; Han, Hyon-Sob
Abstract: Mercury (Hg) is known as a highly toxic heavy metal, and its toxicity varies depending on its form due to different toxicokinetics between inorganic and organic Hg. Limited information on comparison of Hg toxicity concerning its chemical form by oral exposure is currently available in cultured fishes. Therefore, we conducted a comparative study to have a better understanding of distinct toxic effects between mercuric chloride (HgCl2 ) and methylmercury chloride (CH3 HgCl) in Korean rockfish. The 12-weeks dietary exposure of HgCl2 and CH3 HgCl with its graded levels (0.4–6.4 ppm) (2 × 5 factorial design) in the young-of-the-year rockfish (initial weight: 82 ± 0.3 g) resulted in neither interactive nor main effects on whole-organism responses, including growth, feed utilization, and survival. However, the distinct pattern of Hg accumulation between the two forms in dorsal muscle, brain, liver and kidney tissues was observed, showing that the rockfish fed the CH3 HgCl-contained diets exhibited the dose-dependent accumulation throughout the sampling points (1, 2, 4, 8, and 12 weeks post feeding), whereas those fed the HgCl2 -contained diets did not show such response. The CH3 HgCl exposure induced higher oxidative stress and immunotoxicity, reflected by the elevated plasma superoxide dismutase and lysozyme activities, respectively. In addition, the CH3 HgCl-induced alteration in plasma measurements, including the plasma aspartate transaminase activity and total protein level was found. Taken together, the dietary exposure of methylmercury chloride had more pronounced toxic effects than mercuric chloride in the young-of-year rockfish, needed to be taken into consideration for regulation of maximum allowed levels for Hg by its chemical form. Highlights: Dietary-borne methylmercury chloride had higher toxicity than mercuric chloride. Distinct toxicokinetics between the organic and inorganic mercury was found. Immunotoxicity resulting from the methylmercury chloride exposure was detected. Impaired liver function by the methylmercury chloride exposure was observed.